A Effect of shade and organic manure on growth and yield of sarpgandha (Rauwolfia serpentina l.) under teak and poplar based agroforestry system - Kumar, Devendra (Indian Journal of Agroforestry, 2023)
ABSTRACTThe experiment was carried out during 1st experiment from July 2012- December 2013 and 2nd experiment from July 2014-December 2015. A field experiment of Sarpgandha was laid out separately under teak and poplar based agroforestry system and under open condition with fifteen treatments, having organic manures and irrigation schedule with 15 treatment combination, each replicated three times. The plant growth and yield of Sarpgandha differed significantly due to application of organic manures and irrigation schedule at all the growth and yield under teak, poplar and open based condition 1st and 2nd experiment with the pooled. Application of T12 100% FYM+ 20 days Irrigation resulted in higher plant growth viz. plant height, number of leaves per plant, number of branches per plant, collar diameter and root length, yield parameter viz.root fresh weight (g), root dry weight (g), root yield plant-1, root yield plot-1 (kg) and root yield (q ha-1) and economic viz. gross return, net return and Benefit cost ratio. In this experiment the fresh and dry weight of root were highest under all condition with treatment T12 (100% FYM+ 20 days Irrigation) differed significantly due to application of organic manures and irrigation schedule at all the growth stages under teak, Poplar and open based condition. The highest net return was noticed in T12 (435330, 476630, 386330) and the BC Ratio was observed T12 (2.29, 2.41, 2.14) under teak, poplar and open based agroforestry. Final results revealed that Rauwolfia serpentina is a shade tolerant plant and its growth and yield favoured under teak and poplar tree shade, thus can be explored as intercrop under agroforestry. Keywords: Agroforestry, Economic, Sarpagandha, Teak, Yield